Applications of variable speed drive (VSD) in electrical motors energy savings - Saidur, Rahman; Mekhilef, Saad; Ali, Mansouri B.; Safari, Azadeh; Mohammed, Hussein A. (Elsevier, 2012)
Most motors are designed to operate at a constant speed and provide a constant output; however, modern technology requires different speeds in many applications where electric motors are used. A variable speed drive (VSD) is a device that regulates the speed and rotational force, or output torque of mechanical equipment. Effects of applying VSDs are in both productivity improvements and energy savings in pumps, fans, compressors and other equipment. Variable speed drive technology and the importance of controlling the speed of existing motors have fascinated many attentions in the last years with the advent of new power devices and magnetic materials. This paper is a comprehensive review on applications of VSD in electrical motors energy savings. The aim is to identify energy saving opportunities and incorporated costs of applying variable speed drives to the existing applications of electrical motors. Subsequently, economic analysis, payback period and the effect of current and voltage harmonics generated by VSDs are presented. Authors are hopeful to provide useful information for future variable speed drive applications like fans, pumps, chillers, ventilators and heaters.